Development of an Information System for Off-site Appointment Management - อุโมง, วรวิทย์; คงดีจันทร์, วันชนะ; เอี่ยมศรี, ปาณวัฒน์; สกุลนุ้ย, วลัยนุช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to develop an information system for managing off-site appointments in a systematic and accurate manner while reducing scheduling errors, and to evaluate user satisfaction with the developed system. The system was implemented as a web application supporting appointment management, check-in/check-out time logging, status tracking, calendar-based views, and summary reporting. It was developed using Vue.js for the user interface, .NET Core for RESTful API development, PostgreSQL as the database, and Docker containers for deployment. The sample consisted of 20 employees who perform off-site work at New Technology Information Co., Ltd., selected through purposive sampling, and the system was also evaluated by five experts. Data were collected using a five-point Likert-scale satisfaction questionnaire and analyzed using the mean and standard deviation. The results showed that experts reported an overall satisfaction level of “highest” (=4.60, SD=0.47), with access control and security receiving the highest mean score. Users also reported an overall satisfaction level of “highest” (= 4.56, SD=0.50), with usability receiving the highest mean score. In conclusion, the developed system appropriately supports off-site appointment management and work time logging, and it was highly accepted by both experts and users.